Outcome of Conservative Management of Placenta Previa with Accreta Spectrum Disorder by Applying Continuous Squeezing Suture with Cervical Lifting - Batool, Shazia; Aslam, Faiza; Khalid, Aisha; Shaheen, Fouzia; Amin, Yasmeen; Kausar, Samina (Indus Journal of Bioscience Research, 2025)
Objective: To evaluate the effectiveness of the Continuous Squeezing Suture (CSS) as a conservative surgical technique for controlling hemorrhage in placenta previa and placenta accreta spectrum (PAS) disorders, with the aim of reducing the need for hysterectomy. Study Setting: This cross-sectional study was conducted at the Department of Gynecology, DHQ Hospital, Faisalabad, over six months. Duration of Study: From 8 October 2024 to 8 April 2025. Data Collection: A total of 95 women aged 18–35 years with an ultrasound-confirmed diagnosis of placenta previa with PAS (Creta, Increta, Percreta) without bladder or pelvic organ involvement were included. Elective cesarean sections were performed between 37 and 38 weeks of gestation, and the CSS technique was applied intraoperatively to control hemorrhage. Preoperative and postoperative hemoglobin levels were measured, and the mean hemoglobin drop was recorded. Postoperative hematoma formation was assessed clinically. Results: The mean hemoglobin drop postoperatively was 1.19 ± 0.93 g/dL, which, while statistically significant, indicated effective hemorrhage control without excessive blood loss. Hematoma formation occurred in 27.4% of cases, a rate comparable to previous studies. The findings suggest that CSS effectively controls bleeding in PAS cases and may help reduce hysterectomy rates. Conclusion: CSS appears to be a simple, effective, and safe surgical technique for hemorrhage control in placenta previa and PAS disorders, demonstrating comparable hemostatic effectiveness to other conservative surgical techniques. Future research should focus on comparing CSS with ACCSS and other hemostatic suturing methods to further establish its role in reducing the need for hysterectomy and optimizing maternal outcomes.